Removal of pollution accumulated in the process of wastewater discharge from the bottom layer of river systems - Maryshev, Boris Sergeyevich; Parshakova, Yanina Nikolayevna; Ivantsov, Andrey Olegovich; Zubova, Nadezhda Alekseyevna (Computational Continuum Mechanics, 2022)
Three-dimensional numerical simulation has been performed to investigate the transport of impurities in a two-layer system “liquid-porous medium” for different hydrodynamic regimes of river systems. The dynamics of waste water containing heavy impurities in areas of industrial activity is modeled. The parameters of the numerical experiment correspond to the data of full-scale flow experiments in natural water bodies, part of the reservoir where the Solikamsk-Berezniki industrial hub is located. Due to the influx of brines, pollution accumulates in the hyporheic zone of the river, the fluid flow carries this pollution away through the porous medium, thus the problem is solved of washing out the brine distributed in the porous medium. The computational domain consists of a fluid mass (river) propagating over a porous medium (river bottom, hyporheic zone). It is shown that the concentration of polluting ingredients in the soil of the river bottom near the discharge points increases in the presence of "heavy" impurities. Such problems arise acutely when excess highly mineralized brines are discharged into water bodies located in the industrial areas with “heavy” wastewater, for which, due to significant intra-annual fluctuations in the water level and ice cover, the option with near-bottom wastewater disposal is considered preferable.